Why - Living in a War Zone? - Nancy Bauser (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
After a trauma, an illness, a disability or an addiction, life becomes an uphill battle in all situations. Whether it is dealing with doctors, drug companies, mental health or rehabilitation professionals, living as an independent, self-sufficient human being is simply no longer possible. There are countless adjustments, accommodations and modifications that must be made, in order to ensure a quality life will be realized.